The Effect Of Supervision Performance On Fishing Ship Obedience In North Minahasa - Ilham Syah, Bahrul Yusuf Nasruddin; Budiman, Johnny -; Manoppo, Lefrand -; Kaparang, Frangky Erens; Modaso, Vivanda O.J; Sumilat, Deiske Adeline (Sam Ratulangi University, 2021)
Supervision of fishing vessels is one of the efforts to prevent violations in the fishery. The level of compliance of fishing vessels in accordance with the laws and regulations is influenced by the performance of fishery supervisors who act as the spearhead of surveillance activities because of their authority in issuing operational letters. The purpose of this study is to optimize the supervision of marine resources and fisheries in North Minahasa so that it is expected that the level of violations that occur can decrease and state losses can be prevented. The methodology used is (1) Descriptive analysis and calculation of the average weighting of the value of each factor that affects the performance of supervisors; (2) Spearman Rank Analysis to determine the level of relationship of each factor that affects the supervisor's performance level; (3) Analytical Hierarchy Process (PHA) method to improve the performance of fishery ship supervisors in North Minahasa which can also be applied in supervisory units or other regional working areas. From the results of this study can be stated the level of performance of fisheries supervisors in North Minahasa is good. Improving the performance of fishery boat supervisors in North Minahasa can be done by improving the seriousness of performance that can be done by awarding; improved proficiency that affects the quality of inspection results and improvement of facilities and infrastructure that is able to improve the speed of inspection results.Keywords: Ship obedience; Supervisory performance; StrategyAbstrakPengawasan kapal perikanan merupakan salah satu upaya mencegah terjadinya pelanggaran bidang perikanan. Tingkat ketaatan kapal perikanan yang sesuai dengan peraturan perundang-undangan dipengaruhi oleh kinerja pengawas perikanan yang berperan sebagai ujung tombak kegiatan pengawasan karena wewenangnya dalam mengeluarkan surat laik operasi. Tujuan penelitian ini adalah untuk mengoptimalkan pengawasan sumberdaya kelautan dan perikanan di Minahasa Utara sehingga di harapkan tingkat pelanggaran yang terjadi dapat menurun dan kerugian negara dapat tercegah. Metodologi yang digunakan adalah : (1) Analisis deskriptif dan perhitungan rata-rata bobot nilai masing-masing faktor yang berpengaruh terhadap kinerja pengawas; (2) Analisis Rank Spearman untuk mengetahui tingkat hubungan dari masing-masing faktor yang berpengaruh terhadap tingkat kinerja pengawas; (3) metode Proses Hierarki Analitik (PHA) untuk meningkatkan kinerja pengawas kapal perikanan di Minahasa Utara yang juga bisa diterapkan di Satuan Pengawas atau Wilayah Kerja daerah lain. Dari hasil penelitian ini dapat dinyatakan tingkat kinerja dari pengawas perikanan di Minahasa Utara adalah baik. Peningkatan kinerja pengawas kapal perikanan di Minahasa Utara dapat dilakukan dengan cara meningkatkan kesungguhan kinerja yang bisa dilakukan dengan pemberian penghargaan; peningkatan kecakapan yang berpengaruh terhadap kualitas hasil pemeriksaan dan peningkatan sarana dan prasarana yang mampu meningkatkan kecepatan hasil pemeriksaan.KATA KUNCI: Ketaatan kapal; Kinerja pengawas; Faktor Internal dan Eksternal